Giant serpentine aneurysms - Mawad, Michel E. (1995)
PURPOSE To describe the characteristic CT, MR, and angiographic features of giant serpentine aneurysms and discuss their endovascular treatment. METHODS Thirteen patients with giant serpentine aneurysms were studied at our institution in the last 3 years. They all underwent CT and MR studies as well as cerebral angiography. More recently, some of the patients were studied with MR angiography. Seven patients had endovascular occlusion of the giant serpentine aneurysms, 3 with N-butyl cyanoacrylate, 2 with Guglielmi detachable coils, and 2 with detachable balloons. RESULTS Giant serpentine aneurysms mimic cerebral neoplasms on CT and MR studies; they are often associated with mass effect and adjacent edema, and they enhance with contrast medium. The cerebral angiogram shows a residual irregular lumen of the partially clotted aneurysm, which continues into normal branches supplying the distal arterial territory. Six patients were treated successfully with an endovascular approach consisting of complete and permanent occlusion of the parent artery. CONCLUSION Giant serpentine aneurysms from a subgroup of large intracranial aneurysms that have specific CT, MR, and angiographic features, which should be recognized before their treatment. The endovascular treatment of the aneurysm consists of permanent occlusion of the parent artery.